Odpowiedzi

2010-03-04T07:56:43+01:00
0,03x-0,02y= -2 \*100
0,6x+0,5y=590 /*10

3x - 2y = -200 /*-2
6x + 5y = 5900

-6x + 4y = 400
6x +5y = 5900

9y = 6300

y = 700
6x + 3500 = 5900

y = 700
6x=5900 - 3500

y= 700
6x =2400

x = 400
y = 700


0,7x-0,25y=5 /*100
1,5x-0,75y=9 /*100

70x - 25y = 500 /*-3
150 x- 75y = 900

-210x +75y = -1500
150x - 75y = 900

-60x = -600

x = 10
700 - 25y = 500

x = 10
-25y = 500-700

x = 10
-25y = -200

x=10
y=8




nie wiem o co chodzi w trzecim (dziwnie zapisane..)

3(x+2) - 5(y-5)= 2
24x+6y= 2

3x + 6 - 5y +25 = 2
24x + 6y = 2

3x -5y = 2 - 25 - 6
24x + 6y = 2

3x - 5y = -29 /*-8
24x + 6y = 2

-24x + 40y = 232
24x + 6y = 2

46y = 234
nie da sie tak. sorki.. ale nie wiem o co chodzi..